The financial reporting systems quality (FRSQ) and institutional investors: The case of an emerging market - Adel Ali Al-Qadasi; Hamdan Amer Ali Al-Jaifi; Ahmed Hussein Al-Rassas; Ayad Ahmed Al-Qublani (Cogent Business & Management, 2022)
Attracting institutional shareholders in stock markets has drawn the attention of financial market regulators and researchers. Globally, governments are trying to attract institutional investors by reducing information asymmetry and improving governance and transparency, in order to produce a high-quality financial reporting system. Hence, this study investigates the impact of financial reporting systems quality (FRSQ) on institutional ownership. It uses all non-financial listed companies on Bursa Malaysia over the period 2009-2016. Ordinary Least Square (OLS) regression based on two-way cluster-robust standard errors (firm and year) is used to achieve the objective of the study. The findings show a positive relationship between institutional ownership and FRSQ, suggesting that institutional investors prefer to invest in a firm that has effective FRS. The study differs from previous research in terms of capturing the FRSQ based on a wider set of governance attributes, namely audit committee characteristics (size, independence, diligence and expertise), internal audit function (IAF) cost and sourcing arrangements, and external auditors' attributes (audit fees, industry auditor specialist, auditor's reputation and size) that are yet to be examined in either developed or developing countries. It offers insights for regulators in Malaysia and other emerging economies which are in the process of undertaking regulatory reforms in their corporate governance structure. Managers could learn which aspects of corporate governance should be considered to keep their firm in a strong position in terms of its ability to attract institutional investors.
Keywords: 650; Malaysia; emerging market; Financial reporting system; institutional investors